Computer books. - Woods, Mike (Bookseller, 2004)
This article presents information on various books related to computer. "The Complete PC Upgrade and Maintenance Guide," 15th ed., by Mark Minasi is a new version which has been completely reorganized, offering simpler navigation, notes on new PC technologies, and a lowered cover price. It includes a CD-ROM with an instructional video. Another book "Essential Electronics for PC Technicians," by John Fatter is a grounding in electronics fundamentals for hobbyists and professionals alike, containing much of the electronics material that candidates must master to pass the A+ examination.